Composite behaviors of dual meminductor circuits - 郑辞晏 于东升 梁燕 陈孟科 (Chinese physics B, 2015)
This paper focuses on analyzing the composite dynamic behaviors of two meminductors in serial and parallel connec- tions with different polarities. Based on the constitutive relations, two time-integral-of-flux （TIF） controlled meminductors are adopted to theoretically demonstrate the variation of memductance in terms of TIF, charge, flux, and current. By uti- lizing a floating memristor-less meminductor emulator, the theoretical analysis reported in this paper is confirmed via a PSPICE simulation study and hardware experiment. Good agreement among theoretical analysis, simulation, and hardware validation confirms that dual meminductor circuits in composite connections behave as a new meminductor with higher complexity.